EEG power spectral slope differs by ADHD status and stimulant medication exposure in early childhood - Robertson, Madeline M.; Furlong, Sarah; Voytek, Bradley; Donoghue, Thomas; Boettiger, Charlotte A.; Sheridan, Margaret A. (Journal of neurophysiology, 2019)
Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder characterized by hyperactivity/impulsivity and inattentiveness. Efforts toward the development of a biologically based diagnostic test have identified differences in the EEG power spectrum; most consistently reported is an increased ratio of theta to beta power during resting state in those with the disorder, compared with controls. Current approaches calculate theta/beta ratio using fixed frequency bands, but the observed differences may be confounded by other relevant features of the power spectrum, including shifts in peak oscillation frequency and altered slope or offset of the aperiodic 1/ f-like component of the power spectrum. In the present study, we quantify the spectral slope and offset, peak alpha frequency, and band-limited and band-ratio oscillatory power in the resting-state EEG of 3- to 7-yr-old children with and without ADHD. We found that medication-naive children with ADHD had higher alpha power, greater offsets, and steeper slopes compared with typically developing children. Children with ADHD who were treated with stimulants had comparable slopes and offsets to the typically developing group despite a 24-h medication-washout period. We further show that spectral slope correlates with traditional measures of theta/beta ratio, suggesting the utility of slope as a neural marker over and above traditional approaches. Taken with past research demonstrating that spectral slope is associated with executive functioning and excitatory/inhibitory balance, these results suggest that altered slope of the power spectrum may reflect pathology in ADHD. NEW & NOTEWORTHY This article highlights the clinical utility of comprehensively quantifying features of the EEG power spectrum. Using this approach, we identify, for the first time, differences in the aperiodic components of the EEG power spectrum in children with attention-deficit/hyperactivity disorder (ADHD) and provide evidence that spectral slope is a robust indictor of an increase in low- relative to high-frequency power in ADHD.